1993
DOI: 10.1007/bf02244948
|View full text |Cite
|
Sign up to set email alerts
|

Differences in fear motivated behaviors among inbred mouse strains

Abstract: The behavioral performance of inbred mouse strains was examined in animal models of anxiety to evaluate the potential contribution of genetic factors to fear-motivated behaviors. The preference that randomly bred mice and rats exhibit for the enclosed as opposed to the open arms of an elevated maze has been considered a fear-motivated behavior. Pronounced differences were observed in this measure among 16 inbred mouse strains. An estimate of the proportion of the variance attributable to between-strain differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
195
8
4

Year Published

1999
1999
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 412 publications
(234 citation statements)
references
References 32 publications
27
195
8
4
Order By: Relevance
“…It is generally assumed that the various tests of anxiety in rodents, such as the elevated plus maze, open-field arena, and conditioned fear paradigms, measure at least one common underlying trait. Consistent with this hypothesis, Trullas and Skolnick (1993) report that performance in the elevated maze predicts behavior in other animal models of anxiety. In a study comparing inbred mouse strains, they found significant negative correlations between the time spent in the open arms of the elevated maze and amplitude of an acoustic startle or latency to eat in a hyponeophagia test.…”
Section: Introductionmentioning
confidence: 62%
See 1 more Smart Citation
“…It is generally assumed that the various tests of anxiety in rodents, such as the elevated plus maze, open-field arena, and conditioned fear paradigms, measure at least one common underlying trait. Consistent with this hypothesis, Trullas and Skolnick (1993) report that performance in the elevated maze predicts behavior in other animal models of anxiety. In a study comparing inbred mouse strains, they found significant negative correlations between the time spent in the open arms of the elevated maze and amplitude of an acoustic startle or latency to eat in a hyponeophagia test.…”
Section: Introductionmentioning
confidence: 62%
“…When inbred strain means replace individual subject observations, (e.g., Collins et al, 1988, Henderson, 1979Ramos and Mormede, 1998;Trullas and Skolnick, 1993) the influence of test session and environmental history V-C matrices are reduced by a factor of (n per strain) −1 , effectively creating a genotypic correlation matrix when n is even moderately large. Factor analyses of genotypic correlation matrices thus avoid the confounding influences of test session environmental effects.…”
Section: Principal Componentsmentioning
confidence: 99%
“…Since the MPD variables reflect data in alcohol naive strains, the genetic relationship between alcohol consumption and measures of activity and anxiety may reflect the strain differences in locomotor activity and anxiety that exist (e.g., Finn et al, 2003;Trullas and Skolnick, 1993;Wahlsten et al, 2003). With regard to bone mineral density, limited evidence suggests that there is no consistent relationship between high bone mass or strength with selection for high alcohol consumption and/or preference in rat lines (Alam et al, 2005), whereas data from animal models of chronic or excessive alcohol intake suggest that chronic exposure to high alcohol doses can inhibit bone formation (e.g., Wahl et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In an extensive comparison of inbred laboratory mouse strains, Trullas and Skolnick [61] characterized elevated plus-maze behavior on the basis of levels of open arm exploration. Thus, strains exhibiting low levels of open arm activity (e.g., A/J) were described as``high reactive'', while those showing high levels of activity in the open arms (e.g., C3H substrains, BALB/c substrains) were labeled``low reactive.''…”
Section: Discussionmentioning
confidence: 99%